Optimization of Small Run-of-River Hydropower Plant Capacity - Khairullah Yusuf; Yulius Rief Alkhaly; Amalia Amalia (International Journal of Engineering, Science and Information Technology, 2022)
The small hydropower plant with a run-of-river concept are being increasingly adopted in less developed and developed countries. The optimization of the plant capacity is critical in the successful development of the plant. The adoption of the current technology will assist in the optimization of the plant development. The important criteria in the evaluation of the optimization are the energy output and plant factor of the plant. In this study, twelve scenarios by varying the installed capacity in range of 4MW to 7.5MW has been simulated in order to obtain the most optimum installed capacity of the plant. In respect to the installed capacity, by the adopting the same available net head of 246.75 m, the design flow would be in range of 1.872 m3/s to 3.510 m3/s with the probability of the flow exceeds or equal to the design flow in range of 29.2% to 8.9%. In the energy calculation, the amount of 0.063 m3/s has been deducted from the available daily flow for the ecological flow. It shows that the energy output for the plant 4MW and 7.5MW would be in range 23 589 MWhr to 28 636 MWhr, respectively. The plant factor of the plant based on all the scenarios are 67.32% for the 4MW plant and 43.59% for the 7.5MW plant. Based on the hydraulic parameters, it was found that the most suitable type of turbine for the plant would be pelton turbines. Based on the relationship between installed capacity, energy output and plant factor, it concludes that the optimum installed capacity is at 5 MW plant.